Influence of cocoa butter diacylglycerols on migration induced fat bloom in filled chocolates. Issue 10 (13th June 2014) - Clercq, Nathalie De; Depypere, Frédéric; Delbaere, Claudia; Nopens, Ingmar; Bernaert, Herwig; Dewettinck, Koen
<x xml:space="preserve">Abstract</x> As migration induced fat bloom remains one of the major quality issues in composite chocolate products, this study investigated whether cocoa butter based DAGs could delay or prevent this phenomenon. A model system consisting of a plastic cylinder with filling and chocolate was utilized for this purpose. Using an automated image analysis procedure, the surface of the chocolate was examined at regular time intervals to detect the presence of fat bloom crystals. The chocolate was cut into different layers and analyzed by HPLC and DSC to monitor the oil migration. It was noticed that the quality characteristics of the plain chocolates only slightly changed during the 1‐year storage period. DSC thermograms demonstrated that the oil migration was a triggering factor for the re‐crystallization to βVI crystals, protruding through the chocolate surface resulting in a grayer and duller appearance. The model based on Fickian diffusion with a constant diffusivity failed to accurately describe the migration of oil into chocolate. Non‐Fickian behavior occurs as besides migration, interaction between oil and cocoa butter can also play a major role. It was concluded that the presence of DAGs did not delay oil migration, nor prevented the appearance of migration induced fat bloom. <inline-graphic xlink:href="ark:/27927/pgh1fcj5p02" content-type="ejlt201300476-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> The performance of the DAG chocolates containing up to 7.5% DAG on fat base, on the occurrence of fat bloom was evaluated. A model system consisting of a plastic cylinder with filling and chocolate was utilized for this purpose, plain chocolates were used as reference. The figure shows peak area of the main melting peak as determined by DSC, of the top layer as function of storage time for the plain chocolate (a) and chocolates with filling (b) (legend represents the % DAG on fat base). It could be concluded that oil migration from the filling was a triggering factor for the re‐crystallization to βVI crystals, protruding through the chocolate surface resulting in a grayer and duller appearance.